PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MELALUI METODE JIGSAW - Lasmi, Lasmi (JESS (Journal of Education on Social Science); Vol 4 No 2 (2020): Social and Educational Issues in Public ServiceDO - 10.24036/jess.v4i2.280, 2020)
This study aimed to determine the effect of the use of jigsaw cooperative learning on the activeness and learning outcomes of Civics learning in class VIII.1 SMP Negeri 2 Sungayang, Tanah Datar, in the academic year of 2016/2017. The research was conducted through class action research in two cycles, each cycle consisting of two meetings. The data were obtained through quantitative data comes from learning outcomes before and after the action was taken. While qualitative data were obtained through observation towards student activities during the learning process. The data were analysed with percentage techniques. After observing and monitoring the learning process and student learning outcomes in each cycle, it could be concluded that the application of the jigsaw type of cooperative learning could make the learning process to be more active, more concentrated, and the students were more responsible for interactions between them. Student learning outcomes seem to have increased on their own efforts .